Pengaruh Pemberian Minyak Atsiri Aetoxylon sympetalum terhadap Tingkat Ketahanan Fokus Mahasiswa Tahun Pertama Fakultas Kedokteran - Nova Primadina; Nilam sari; Yelvi Levani; Nur Aisah Ibrahimiyah (Universitas Muhammadiyah Surabaya, 2025)
First-year medical students tend to experience stress, which can affect how they maintain focus on their work. One alternative treatment that can be done is through relaxation techniques using aromatherapy in the form of essential oils. Crocodile agarwood (Aetoxylon sympetalum) is one of the plants that can provide anxiolytic and antidepressant effects that can be associated with these problems. This study aims to determine the effect of giving Aetoxylon sympetalum essential oil on the level of ability to maintain the focus of first-year students of the medical faculty. This quasi-experiment research method with a nonequivalent control group design was conducted on 34 samples which were divided into control and treatment groups with the same number to see the effect of essential oil on both groups. The research data were analyzed using Spearman's rho test and showed a significance value of 0.004 and a correlation coefficient value of 0.661, meaning that a significant correlation was obtained, the level of correlation between variables was strong and unidirectional. So it can be concluded that the more often inhaling Aetoxylon sympetalum essential oil, the ability to maintain focus will increase.